α-Amanitin resistance is developmentally regulated in carrot - Pitto, L. (1985)
Carrot cells are capable of inactivating α-amanitin only in embryogenic conditions (regenerating cells and embryoids). Instead, the mutant line a3 is capable of inactivating the drug also in nonembryogenic conditions (vegetative growth). The mutation is dominant in somatic hybrids and is pleiotropic, allowing expression during vegetative growth of other embryonal functions. The inactivation of α-amanitin is due to the oxidative activity of tyrosinase.